A study of the response of the root meristem of maize to fractionated and protracted doses of ionizing radiation - Hering, Egbert Raymond (Department of Human Biology, 2020)
Vicia faba and investigating the effects of ionizing radiation on its root system. In particular, species such as Tradescantia, Pisum, Allium and Mordeum vulgare have been extensively studied. Nevertheless an ever-increasing number of workers have used Vicia faba for explaining the basic problems of radio biology. One of the reasons is the small number of large chromosomes contained in the root meristem cells, which are particularly conducive to simple cytological analysis. The seedlings also have other attractive features.